Bahasa Arab: تحليل تغير قيمة النقود في منظور الشريعة الإسلامية / Analysis of the Change in The Value of Money in The Perspective of Islamic Law - Moch. Zainuddin (Fakultas Syariah IAIN Kediri, 2022)
The problem of changes in the value of money, and the continuous fluctuation in its purchasing value, is one of the major problems that we face today. People wonder about the Sharia ruling on changes in the value during the term of the term, in the loan or deferred sale and other obligations related to the liability, and is the obligor required to fulfill the same What is his commitment or worth?. This research is a desk and applied study of the impact of changing the purchasing value of money in Islamic jurisprudence and economics, an applied study in contemporary financial transactions issues. The results of the research are that money is an idiomatic issue, and it does not have a specific form or substance required for it, and everything that people use as money or a standard can be cash, and what people call money is applied to the provisions of money such as the prohibition of usury and the obligation of zakat on it. Paper money is a special type of money, to which the provisions of money apply, but it is unique to its own provisions, including the need to take into account the change in its value. تعد مشكلة تغير قيمة النقود، والتذبذب المستمر في قيمتها الشرائية من المشكلات الكبيرة التي نواجهها اليوم، ويتساءل الناس عن حكم الشريعة في تغير القيمة هذه في فترة الأجل، في القرض أو البيع الآجل وغيرهما من الالتزامات المتعلقة في الذمة، وهل يطلب إلى الملتزم أن يفي بمثل ما التزمه أم بقيمته؟ يعتبر هذا البحث من الدراسة المكتبية والتطبيقية لأثر تغير القيمة الشرائية للنقود في الفقه والاقتصاد الإسلامي، دراسة تطبيقية في قضايا المعاملات المالية المعاصرة. ونتائج البحث هي أن النقود مسألة اصطلاحية فلا يشترط لها شكل معين أو مادة معينةـ، وكل ما يصطلح الناس عليه نقودا أو معيارا يمكن أن يكون نقدا، وما اصطلح عليه الناس نقودا تطبق عليه أحكام النقود كمنع الربا ووجوب الزكاة فيه.والنقود الورقية نوع خاص من النقود، تنطبق عليها أحكام النقود، إلا أنها تنفرد بأحكام خاصة بها، ومنها وجوب مراعاة التغير في قيمتها.